Meningkatkan Pengembangan Bahasa Anak Usia Dini Melalui Media Gambar - Retnaningrum, Wulandari (STAIT Yogyakarta, 2019)
This study aimed to describe an increased process and result of language development through picture media for children Grub A in PAUD AL-Badawi, Purworejo. This research uses methods of classroom action research. This research is done during two cycle. For every cycle consist of four step are: planning, doing, action, observation, and reflection. Planning be list in lesson plan for every cycle that have arranged by teacher. Result of reflection been the next foundation. Subject research is children of Group A PAUD Al-Badawi.Technique of collected data were done by observation, interview and documentation study. Data that collected than were analized discriptive qualitative and quantitative. Result study showed language development of children before action still in begin to developing 62,56%; result study for cycle I up to 73,87%, still in develop category and cycle II up to 85,11% is very develop category. Used picture media have effecting is very good, that is showed by language development of children is increasingly better than before in action use picture media.